Dumping to the abyss: single-use marine litter invading bathyal plains of the Sardinian margin (Tyrrhenian Sea). (October 2018) - Cau, Alessandro; Bellodi, Andrea; Moccia, Davide; Mulas, Antonello; Pesci, Paola; Cannas, Rita; Pusceddu, Antonio; Follesa, Maria Cristina
Abstract: This study reports data on benthic litter abundance, composition and distribution obtained during deep-sea trawl surveys conducted along the Sardinian continental margin down to the bathyal plain, at depths comprised from 740 to 1740 m. None of the investigated sites was litter free. Density ranged from a minimum of 4 to a maximum of >1300 litter items per km 2, with a mean value of 258 ± 59 items. Plastic accounted for 56% of the total collected items, followed by glass (24%), metal (10%). Most items, irrespectively of the category, were single-use items. Fish abundance in all of the investigated catches was significantly higher than the number of litter items, the weight of which was similar to the reared fish biomass. Our results confirm that anthropogenic waste has reached the deep Mediterranean Sea, and that the most recent EU legislation banning single-use plastic tools represents a timely and necessary measure. Highlights: 25 sites from Sardinian bathyal plain were investigated through trawl survey. Plastic was the most abundant category, followed by glass and metal. Single-use items were the dominant category of benthic litter. Density of biological catches was significantly higher compared to litter density. Weight of biological catches was similar to benthic litter mass, regardless depth.